2020
DOI: 10.4236/jss.2020.89021
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation Challenges for International Students in Turkey

Abstract: The number of international students has increased greatly in the past few years. As part of the efforts to internationalize its higher education, Turkey is one of the top destinations for international students hosting over 100 thousand international students by 2018. Research shows that with the increasing number of international students come socio-cultural and academic adaptation challenges. This study employed a qualitative approach to understand the adaptation challenges international students face in Tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…Adaptability is a person's capacity to adjust emotionally, physically, cognitively, and behaviorally in order to function effectively in a new environment (Makhmutova et al, 2018). The adaptability of international students refers specifically to their ability to adjust to the overall environment in their host country (Gebru & Yuksel-Kaptanoglu, 2020). Adaptability has also been evaluated in relation to the amount of stress international students experience (Muraru et al, 2020).…”
Section: Adaptability Of International Studentmentioning
confidence: 99%
See 1 more Smart Citation
“…Adaptability is a person's capacity to adjust emotionally, physically, cognitively, and behaviorally in order to function effectively in a new environment (Makhmutova et al, 2018). The adaptability of international students refers specifically to their ability to adjust to the overall environment in their host country (Gebru & Yuksel-Kaptanoglu, 2020). Adaptability has also been evaluated in relation to the amount of stress international students experience (Muraru et al, 2020).…”
Section: Adaptability Of International Studentmentioning
confidence: 99%
“…This is likely due to the fact that most nations strive to internationalise their education systems, especially their higher education systems (de Wit, 2019). As a result, these nations offer enticing incentives, such as scholarships, study aid, and infrastructures for higher education (Gebru & Yuksel-Kaptanoglu, 2020). Supporting students so they can easily adapt to the learning environment may be one of the most effective ways to attract and retain international students (de Wit, 2019; Hussain & Shen, 2019;Gebru & Yuksel-Kaptanoglu, 2020).…”
Section: Adaptability Of International Studentmentioning
confidence: 99%
“…Turkey is one of the favorite countries for prospective students from all over the world who will study science from various fields (Gebru & Yuksel-Kaptanoglu, 2020). As in the field data findings, several factors caused Indonesian students to choose Turkey as a place to recite and study science, as shown in the following table: Affordable cost Prospective Indonesian students are interested in studying in Turkey regarding the low cost of living but still comfortable and prosperous for students and thus becomes a magnet and a strong attraction for prospective students in Turkey.…”
Section: Psychological Well-being Of Indonesian Students Studying In ...mentioning
confidence: 99%
“…Lack of confidence in mastering a foreign language also becomes an obstacle for a new student to adapt and establish positive relationships with other friends; in the end, it fades familiarity and is unable to establish good cooperation between students. c. Low Environmental Mastery Facts on the ground also show that some students had low mastery of the new environment (Gebru & Yuksel-Kaptanoglu, 2020). Mastery of the environment is one of the things determining the fast and slow periods of self-adaptation.…”
Section: B No Positive Relationships With Othersmentioning
confidence: 99%
“…The biggest adaptation problem for international students stems from cultural differences (Çetin et al, 2017;Gebru & Yuksel-Kaptanoglu, 2020). The difference between the society in which a person grew up and the culture he / she…”
Section: Cultural Adaptationmentioning
confidence: 99%